Level of Satisfaction Towards the Services Offered by Millennium Distribution System Incorporation among Their Registered Retailers in Tangub City - Cabanday, Dixie A.; Calvo, Chiery Pearl R.; Muñez, Sanchai S.; Magsayo, Eliaquim T.; Morales, Arlyn V. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Level of satisfaction plays a crucial role in guiding the company through maintaining the loyalty of their registered retailers.  This study was conducted to determine the level of satisfaction towards the services offered by Millennium Distribution System Incorporation (MDSI) among their registered retailers in Tangub City.  A descriptive-quantitative research design was used. A total of 156 registered retailers using an adopted-modified survey questionnaire.  The study was carried throughout the academic year 2024-2025 in the second semester.  The findings revealed that registered retailers strongly agree with the services offered by the company, particularly ordering service quality and delivery service quality, which further implies a very high level of satisfaction.  However, visual merchandising is the least factor that the registered retailers agreed, which further implies a high level of satisfaction.  This implies that the services offered by the Millennium Distribution System Incorporation in Tangub City have their retailers’ interest in mind.  The study concluded that all service factors contribute to retailer satisfaction and that the company’s sales agents and personnel are fulfilling their responsibilities effectively.  These findings may assist MDSI in reinforcing its goal of delivering excellent and high-quality services to its registered retailers.